PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS PEGAWAI PADA KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TORAJA UTARA - Linggi, Hermin Yanti Toding; Tangkeallo, Dian Intan; Tangdialla, Randi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research aims to test and determine the influence of work discipline and work environment on employee productivity at the North Toraja Regency Population and Civil Registration Service Office. This research method uses quantitative research. Data collection techniques were through questionnaires. The population and sample in this study were all employees at the Population and Civil Registration Office of North Toraja Regency. Data were analyzed using the SPSS 26 program.The calculation results from the t test on the work discipline variable t count 3,420> t table 1,688 and on the work environment variable the t count value 10,055 > t table 1,688. This research shows that, partially work discipline has an effect on employee productivity, the work environment has an effect on employee productivity and simultaneously work discipline and work environment influence employee productivity at the North Toraja Regency Population and Civil Registration Service Office.